Integral equations calculations and computer simulations of the static structure and ionic transport in molten nickel halides - Tasseven, C; Alcaraz, O; Trullas, J; Silbert, M (FREUND PUBLISHING HOUSE LTD, 1998)
We present the first integral equations calculations and computer simulations of the static structure and ionic transport properties of molten nickel dihalides near melting. The calculations have been carried out using the hypernetted chain theory of liquids (HNC), and for the simulations we have used molecular dynamics (MD). The potentials used for the calculations have a similar functional form as the semiempirical potentials originally proposed by Vashishta and Rahman in 1978 (Phys. Rev. Lett., 40, 1337) to study alpha-AgI. The results for both the pair distribution functions and partial structure factors are in fair agreement with experiment, except for the cation-cation partials where agreement is poor, particularly at small momentum transfer. Most of, but not all, the differences with experiment are likely to be due to the use of a pairwise additive rigid ion model potential. There is, to our knowledge, no experimental information on the ionic transport properties for the NiX2 melts (X = Cl, Br, I). We believe that our predicted results for the self-diffusion coefficients and ionic conductivity are likely to overestimate the experimental values when these become available. The results for the velocity autocorrelation functions suggest a transport mechanism akin to that present in the alkali halides. We find no evidence of remnants of superionic behaviour in molten NiI2.
Keywords: SILVER-IODIDE MELTS; MOLECULAR-DYNAMICS; COPPER HALIDE; CHLORIDE; AGI; POTENTIALS; MIXTURES; LIQUIDS; Materials Science